2019
DOI: 10.18632/aging.102451
|View full text |Cite
|
Sign up to set email alerts
|

Studies on APP metabolism related to age-associated mitochondrial dysfunction in APP/PS1 transgenic mice

Abstract: The aging brain with mitochondrial dysfunction and a reduced adenosine 5’-triphosphate (ATP) has been implicated in the onset and progression of β-Amyloid (Aβ)-induced neuronal toxicity in AD. To unravel the function of ATP and the underlying mechanisms on AD development, APP/PS1 double transgenic mice and wild-type (WT) C57 mice at 6 and 10 months of age were studied. We demonstrated a decreased ATP release in the hippocampus and platelet of APP/PS1 mice, comparing to C57 mice at a relatively early age. Level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…This suggests that the lower resting state CMRO 2 does not simply result from restricted access to oxygen due to limited blood flow, but rather indicates altered mitochondrial function. This is consistent with previous studies in aged APP/PS1 that have reported decreased COX and SDH activity [ 28 ], as well as lower PGC1α and Tfam protein levels [ 29 ], suggesting a mitochondrial impairment in this model. Resting state CBF might nonetheless be regionally impaired in APP swe /PS1 dE9 , which would not necessarily be captured by our analysis over 8 voxels and/or might not reach significance given our small sample size.…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that the lower resting state CMRO 2 does not simply result from restricted access to oxygen due to limited blood flow, but rather indicates altered mitochondrial function. This is consistent with previous studies in aged APP/PS1 that have reported decreased COX and SDH activity [ 28 ], as well as lower PGC1α and Tfam protein levels [ 29 ], suggesting a mitochondrial impairment in this model. Resting state CBF might nonetheless be regionally impaired in APP swe /PS1 dE9 , which would not necessarily be captured by our analysis over 8 voxels and/or might not reach significance given our small sample size.…”
Section: Discussionsupporting
confidence: 93%
“…Mitochondrial dysfunction is known to be an early event in both APP/PS1 mice (Chen et al, 2019) and human AD brain pathology (Hauptmann et al, 2009;Moreira et al, 2007;Nunomura et al, 2001), and is believed to play a role in the synaptic loss that occurs early in the disease process (Du et al, 2012). Downregulated synthesis of mitochondrial proteins, specifically the oxidative phosphorylation-associated proteins Ndufs5, Ndufa12, Cox4i1 and Cox6b in the asymptomatic APP/PS1 mice could underlie the decreased electron transport chain capacity observed in this and other models of AD-like pathology (Bo et al, 2014;David et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction is known to be an early event in both APP/PS1 mice 58 and human AD brain pathology [59][60][61] , and is believed to play a role in the synaptic loss that occurs early in the disease process 62 . Downregulated synthesis of mitochondrial proteins, specifically the oxidative phosphorylation-associated proteins Ndufs5, Ndufa12, Cox4i1…”
Section: Discussionmentioning
confidence: 99%